(untitled) (London Journal of Engineering Research, 2025)
The article is devoted to the understanding of the world as an object consisting of systems, as separate “bricks”, despite their diversity. Non-living systems develop according to the laws of natural sciences: physics, chemistry, astronomy. Their development is not targeted, while there is an increase in disorder (entropy). Living systems strive to survive and expand, while they transform everything around them to improve their existence. Disorder (entropy), from the point of view of living systems (in relation to the achievement of a goal), decreases. A general classification of the systems of the surrounding world is given. The evolution of living systems and the features of their development are explained